Territorial upscaling of local governments: a variable-oriented approach to explaining variance among Western European countries. Issue 4 (4th July 2017) - Askim, Jostein; Klausen, Jan Erling; Vabo, Signy Irene; Bjurstrøm, Karl
ABSTRACT: Local government systems change at varying speeds. While some countries have dramatically reduced the number of local governments during a short period of time, other countries have seen only incremental change or relative inertia. A number of explanations for structural change have been put forward in the comparative local government literature, but these explanations have to a small extent been tested empirically. This article uses statistical indicators to analyse changes in the local government systems in 17 Western European countries between 2004 and 2014. Some often-cited explanations for what drives structural change receive little support. Still, the article demonstrates that changes tend to occur in situations marked by different combinations of decentralisation, urbanisation, fiscal stress and a recent history of territorial upscaling.